2012
DOI: 10.1002/mats.201200007
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic Monte Carlo Studies on the Importance of the Reaction Scheme in Segmental Exchange of Copolymer Chains

Abstract: Kinetic Monte Carlo studies (confirmed by integration of the corresponding differential equations) are used to demonstrate the fundamental differences between the two most often accepted schemes of segmental exchange. Modeling of reshuffling systems, originally composed of homopolymers of various $\overline {DP} _{{\rm n}} $, various mass distributions, and different compositions, is carried out until the equilibrium copolymers are obtained. It is shown that one of the schemes leads always to a random microstr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 22 publications
0
16
0
Order By: Relevance
“…Our previous studies have shown that equilibration time of copolymer microstructure corresponds to a certain number of attacks on an average copolymer unit (about 7, depending on the reshuffling rate constants), independently of copolymer DP n . [9] Taking this into account our results are understandable: the same time is needed to get the same average number of reshuffling attacks on a copolymer unit independently of copolymer DP n because reshuffling rate is proportional to DP n for the same concentration of active Table 1. species. This time corresponds to equilibration time unless reshuffling is not too fast.…”
Section: Equilibration Timesmentioning
confidence: 77%
“…Our previous studies have shown that equilibration time of copolymer microstructure corresponds to a certain number of attacks on an average copolymer unit (about 7, depending on the reshuffling rate constants), independently of copolymer DP n . [9] Taking this into account our results are understandable: the same time is needed to get the same average number of reshuffling attacks on a copolymer unit independently of copolymer DP n because reshuffling rate is proportional to DP n for the same concentration of active Table 1. species. This time corresponds to equilibration time unless reshuffling is not too fast.…”
Section: Equilibration Timesmentioning
confidence: 77%
“…By the way, the name of this parameter seems to be incorrect and therefore the quotation marks are used in this paper–see the discussion on this subject in our previous paper . The value of RD being smaller than unity is in contradiction with understanding of thermodynamics of segmental exchange because it indicates (contrary to expectation based on the assumed rate constants) deviation from randomness towards the increased contribution of homo‐dyads.…”
Section: Introductionmentioning
confidence: 87%
“…The importance of the principle of microscopic reversibility (microreversibility) in copolymerization systems with reshuffling of copolymer units was already discussed . One of consequences of this principle is a necessary agreement between the microstructure of copolymer stemming from thermodynamics and that stemming from segmental exchange processes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, this does not necessarily mean the absence of Ru-carbene complex selectivity with respect to NB or COE units. According to the theory of interchange reactions involving chain ends [14], the fully random chain structure is attained when k NB-NB k COE-COE = k NB-COE k COE-NB , where k α-β is the elementary rate constant describing the attack of an α terminal unit on a β internal unit. As is seen from Fig.…”
Section: Nb = [I(c CD )+I(c a )]/I(c A ) L Coe = [I(c Ef )+I(c mentioning
confidence: 99%